2015
DOI: 10.1097/pep.0000000000000173
|View full text |Cite
|
Sign up to set email alerts
|

Behavior During Tethered Kicking in Infants With Periventricular Brain Injury

Abstract: Purpose Describe behavior of children with periventricular brain injury (PBI) in a tethered-kicking intervention. Methods Sixteen infants with PBI were randomly assigned to exercise or no-training in a longitudinal pilot study. Frequency of leg movements and inter-limb coordination were described from videos at 2 and 4 months corrected age (CA). Results Eight of 13 children (62%) with longitudinal data increased the frequency of leg movements while tethered to a mobile between 2 and 4 months CA. Movement f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…They reported on 10 independent studies. Six additional publications ( 24 29 ) correspond to supplementary analyses of four of the 10 selected ( 30 33 ). Consequently, these six publications are not reported here because they used the same cohorts and protocols as studies that were already included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported on 10 independent studies. Six additional publications ( 24 29 ) correspond to supplementary analyses of four of the 10 selected ( 30 33 ). Consequently, these six publications are not reported here because they used the same cohorts and protocols as studies that were already included.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a more sensitive developmental scale such as the TIMP might have been used instead of the AIMS to evaluate the effects of the motor training, as AIMS norms have been found to contradict medical diagnosis on several occasions [see Cameron et al ( 38 )] ( 33 ). We should note that one subsequent publication [see Campbell et al ( 29 )] ( 28 ), which is not reported in detail here to avoid repetition, analyzed the effect of kicking training alone between 2 and 4 months in the same population trained in Campbell et al ( 29 ). However, no more positive results were reported.…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review identified 17 unique controlled trials using CPBI for improving feeding, motor, and cognitive outcomes in infants 28–32,34–37,39,40–43,45–47. Our review suggests that interventions based on contingency paradigms have potential for application to physical therapy practice, starting from NICU to early intervention in infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen studies used contingency paradigms as either the primary or one of the key components of intervention to improve motor and cognitive outcomes in infants. 31,32,[34][35][36][37][39][40][41][42][43]46,47 Eleven studies included term born infants 31,32,[34][35][36][37][39][40][41]45,47 (n = 421) and 3 studies included preterm infants 42,43,46 (n = 63) resulting in a total of 484 infants across the 14 studies. Age at treatment onset had a range of 2 to 5 months.…”
Section: Cpbi For Motor and Cognitive Outcomesmentioning
confidence: 99%
See 1 more Smart Citation